How do Japanese schools promote parental involvement? - Jabar, Melvin A. (Animo Repository, 2010)
This study describes the different practices in Japanese elementary and junior high schools aimed at forging partnerships between teachers and parents and among parents through parental involvement. The different types of parental involvement are arranged following Greenwood and Hickman’s typology (1991) namely, parents as audience, volunteers, paraprofessionals, teachers, learners, and decision makers. Additionally, two other types of parental roles—parents as partners of teachers and other parents—are identified. The data for this paper were drawn from the author’s limited participant observation in Japanese schools as part of a larger doctoral study on educational outcomes and experiences of bicultural children in Japan. This paper aims to contribute to the different approaches in understanding parental involvement.